ASSESSMENT OF INDOOR NON-IONISING RADIATION OF SELECTED RESIDENTIAL APARTMENTS IN GOMBE METROPOLIS, GOMBE STATE, NIGERIA - A.Y, OCHU; A, SABO; T, GARBA (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2022)
A cross sectional design approach was employed to assess the indoor radiation exposure of population in selected residential apartments in Gombe Metropolis, Gombe State Nigeria. Primary data was obtained aided by a hand-held radiation meter and a well-structured questionnaire. With the aim of ascertaining the radiation distribution pattern and occurrence rate of Electro Hypersensitivity Syndrome’ (EHS) in the study area. The analysis of variance test ‘ANOVA’, an inferential statistics was used to ascertain the radiation distribution pattern, while the descriptive statistics was used in determining the occurrence rate of (EHS) in populations of the study area. A convenience sampling technique was adopted, and 30 sampling unit of residential apartment were chosen for the study, relying on homogeneity, inclusion and exclusion criteria. The pre-tested questionnaire scored 74% Cronbach's Alfa reliability. Findings from the study revealed that total indoor radiation varied significantly across the study area, with F(2,27) = 38.599, P < 0.00, at (α = 0.05). The occurrence rate of the understudied EHS illnesses were determined to be in the following order: sleep disorder, fatigues, headaches, dizziness, loss of appetite and memory loss, with mean averages of 3.53, 3.26, 2.97, 2.70, 2.17, and 2.03 respectively. Hence a recommendation for public sensitization on the occurrence, effect and necessary policy control measures, towards minimising public exposure to indoor non-ionising radiation, by relevant stakeholders such as: the Standards Organisation of Nigeria, Federal and States Ministries of Environment and the Nigerian Customs was necessitated.